(untitled) - Reeve, Roger N. (Chichester, 1994)
Environmental Analysis As the study of the environment has become increasingly important, so the number of analytical techniques employed has grown dramatically. Environmental Analysis is a textbook which comprehensively surveys the most important analytical chemistry methods now used in this field. All the main areas of environmental analysis are covered. The first two chapters introduce the concepts necessary for a study of the environment. They enable the reader to gain an understanding of how pollutants may be transported in the environment, and the role of analytical chemistry in the monitoring of these pollutants. The remaining six chapters cover the analysis of water, solid and atmospheric samples. The special problems of ultra-trace analysis are also considered. A number of problems are included at the end of each chapter. Environmental Analysis is an invaluable text for all students of environmental analysis and environmental science. A basic knowledge of analytical techniques is assumed, but the author has employed a style which enables the book to be used by environmental scientists without a background in chemistry. Analytical Chemistry by Open Learning This series provides a uniquely comprehensive and integrated coverage of analytical chemistry, covering basic concepts, classical methods, instrumental techniques and applications. The learning objectives of each text are clearly identified and the student’s understanding of the material is constantly challenged by self assessment questions with reinforcing or remedial responses. The overall objective of Analytical Chemistry by Open Learning is to enable the student to select and apply appropriate methods and techniques to solve analytical problems, and to interpret the results obtained.
Keywords: Hóa học môi trường,Hóa học, phân tích,Environmental chemistry,Chemistry, Analytic; Hướng dẫn lập trình,Hướng dẫn lập trình,Programmed instruction,Programmed instruction